Intra- and Intersession Repeatability of a Double-Pass Instrument - Vilaseca, Meritxell; Peris, Elvira; Pujol, Jaume; Borras, Rosa; Arjona, Montserrat (Optometry and vision science, 2010)
To evaluate the intra- and intersession repeatability of the optical quality parameters provided by the Optical Quality Analysis System (OQAS), which is based on the double-pass technique. We performed optical quality measurements using the OQAS on 20 eyes of 10 healthy subjects who had best spectacle-corrected visual acuity of 20/20 or better. Measurements were performed by the same examiner in three different sessions that were separated by 10-min intervals. The subject's eye was realigned at the beginning of each session. During each session, three consecutive measurements were taken without realignment. The following optical quality parameters were analyzed: the modulation transfer function cutoff frequency (MTFcutoff), the Strehl ratio, the OQAS values (OV) at contrasts of 100%, 20%, and 9%, and the objective scatter index (OSI). The mean coefficients of repeatability obtained for the first session were 4.51 (MTFcutoff), 0.049 (Strehl ratio), 0.15 (OV 100%), 0.21 (OV 20%), 0.28 (OV 9%), and 0.11 (OSI), which were similar to those found in the second and third sessions. The confidence limits in the Bland and Altman charts when the intrasession repeatability was assessed (in a comparison of the first and second measurements of the first session) ranged from -3.16 to 3.94 (MTFcutoff), -0.060 to 0.069 (Strehl ratio), -0.12 to 0.18 (OV 100%), -0.20 to 0.23 (OV 20%), -0.29 to 0.27 (OV 9%), and -0.12 to 0.13 (OSI). The same limits when the intersession repeatability was assessed (in a comparison of the first and second sessions) ranged from -5.30 to 5.49 (MTFcutoff), -0.054 to 0.050 (Strehl ratio), -0.17 to 0.17 (OV 100%), -0.22 to 0.19 (OV 20%), -0.26 to 0.29 (OV 9%), and -0.12 to 0.13 (OSI). Our findings showed that OQAS is a clinical instrument with a good intra- and intersession repeatability and that the realignment of the eye does not introduce any additional variability in the measurements.